Now is the time: VFR travel desperately seeking respect. (19th January 2022) - Zentveld, Elisa; Labas, Alan; Edwards, Steve; Morrison, Alastair M.
Abstract: Visiting friends and relatives (VFR) is a significant form of travel in most countries. However, relatively little VFR research has been undertaken, and few destinations have developed dedicated VFR marketing campaigns. However, altered conditions have created a different environment. People unable to see friends and family due to lockdowns are focused on reconnecting. There has been a shift in economic conditions, travel opportunities, safety, and connections. This article presents three components: (a) the psychology of lockdowns in reducing social connections; (b) a content analysis on VFR travel; and (c) recommendations on capitalising on VFR travel.